2017
DOI: 10.1055/s-0036-1588555
|View full text |Cite
|
Sign up to set email alerts
|

Indium(III)-Catalyzed Transformations of Alkynes: Recent Advances in Carbo- and Heterocyclization Reactions

Abstract: The use of a well-chosen catalyst is instrumental for the development of more efficient, economical and environmentally friendly reactions. In recent decades, indium-based catalysts have proven to be competitive and useful alternatives to transition-metal catalysts such as silver and gold. In this short review, we present some of the recent advances in indium(III)-catalyzed transformations of alkynes, with a focus on cyclization reactions.1 Introduction2 Terminal Alkynes as Nucleophiles3 Nucleophilic Additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Indium(III) has recently been shown to be a powerful π-Lewis acid for activating unsaturated systems, especially alkynes. [98] Dual Lewis acid activity of Indium(III) has found useful uses in the production of complex chemical molecules. [99] A process based on the indium(III) π-Lewis activation of the alkyne is further supported by computational studies.…”
Section: Miscellaneousmentioning
confidence: 99%
See 1 more Smart Citation
“…Indium(III) has recently been shown to be a powerful π-Lewis acid for activating unsaturated systems, especially alkynes. [98] Dual Lewis acid activity of Indium(III) has found useful uses in the production of complex chemical molecules. [99] A process based on the indium(III) π-Lewis activation of the alkyne is further supported by computational studies.…”
Section: Miscellaneousmentioning
confidence: 99%
“…Indium(III) has recently been shown to be a powerful π‐Lewis acid for activating unsaturated systems, especially alkynes [98] . Dual Lewis acid activity of Indium(III) has found useful uses in the production of complex chemical molecules [99] .…”
Section: Metal‐catalysed Synthesis Of Benzofuransmentioning
confidence: 99%
“…2 Indium is an air- and moisture-stable non-toxic metal which has gained recent importance for the formation of carbon–carbon bonds. 3,4 The indium-mediated reaction between carbonyls and allyl or propargyl bromides resulted in the formation of allylic (Scheme 1a) 5 or allenic/propargylic alcohols (Scheme 1b), 6 respectively. On the other hand, butenolide-based structures have received considerable interest.…”
Section: Introductionmentioning
confidence: 99%
“…Later studies have shown that cationic group 13 complexes show catalytic activity in synthesis ranging from fine chemicals to polymers. , Their reactivity is commonly attributed to enhanced Lewis acidity, which leads to stronger activation of substrate molecules. , Lewis acidity has been described as an inherent property of metals in explaining reactivity patterns. For example, the lower reactivity of indium complexes compared to their gallium analogues has been attributed to the weaker Lewis acidity of the indium species; however, this assumption is not supported by significant experimental or computational data.…”
Section: Introductionmentioning
confidence: 99%